TREN PENELITIAN KINERJA BUMN, STUDI BIBLIOMETRIK - Nusantara, Aji Cahya; Widarjo, Wahyu; Arifah, Siti; Prasetyanto, Didik (Jurnal Akuntansi, 2024)
This study offers empirical evidence of the SOE performance research publishing trend and variables associated with the role of accounting, before and during the COVID-19 pandemic, so that it can be used as a direction for further research and publication. A total of 996 articles were collected by searching for the keywords company performance, SOE, and accounting role, for the 2012-2021 period from the Google Scholar page, then analyzed using the VOS viewer application. Research publications on the topic of SOE performance over the last decade consisted of the period before and during the COVID-19 pandemic, has shown a significant come down in number. The findings indicate that the volume of publication on the subject of SOE performance has increased related to the role of accounting is uneven in several journals or publishers, but only a several journals dominate publications related to this topic. In addition, the research results show the development of variables related to the performance of SOEs and accounting role such as ‘corporate governance’, ‘state ownership’, ‘disclosure’, ‘board’, capital structure’, and ‘assets’ variables. The results of the VOS viewer analysis cannot read the connection with micro values, especially the development of publications in 2021.